HAK IJBAR WALI DALAM PERKAWINAN WANITA HAMIL DI LUAR NIKAH DENGAN SELAIN LAKI- LAKI YANG MENGHAMILI PERSPEKTIF MADZHAB SYAFI’I - Huda, Afiful; Qurotul Aini, Siti Maryam; `Fadilah, Umi Nuril (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2023)
The problem that arises is that when a girl is already pregnant during dating, but a guardian does not approve if his daughter marries the man who impregnated her. The guardian wants to marry his daughter to another man who is considered better than the man who impregnated his daughter. The author wants to further examine the opinions of the Hanafi and Shafi'i schools of thought regarding the guardian's right to compel in marriage. The type of research used by the author is library research, while for the research approach, the researcher uses a qualitative approach. The results of the study show that according to the Shafi'i school of thought, a guardian cannot use his right to compel in the marriage of a pregnant woman outside of marriage or due to adultery. However, a guardian can use his discretionary right, which must be approved by the pregnant woman, in the form of a statement. Because the reason for compulsory guardianship according to the Shafi'i school of thought is the preservation of virginity.